1998
DOI: 10.1136/adc.78.6.536
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, tolerance, and pharmacokinetics of once daily tobramycin for pseudomonas exacerbations in cystic fibrosis

Abstract: Objective-To compare once daily with thrice daily tobramycin for treatment of Pseudomonas aeruginosa infection in patients with cystic fibrosis. Design-22 patients with cystic fibrosis, mean (SD) age 11 (3.4) years (range 5.6-19.3), with pulmonary pseudomonas exacerbations were randomly assigned to receive a 14 day course of tobramycin (15 mg/kg/day) either in three infusions (group A) (n = 10) or a single daily infusion (group B) (n = 12), combined with ceftazidime (200 mg/kg/day as three intravenous injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 20 publications
5
90
1
Order By: Relevance
“…Once daily dosing of amikacin and tobramycin achieves higher airway concentrations than multiple daily dosing [68]. The general applicability of once daily dosing is, however, pending.…”
Section: Penetration Of Antibiotics Into Respiratory Secretions and Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Once daily dosing of amikacin and tobramycin achieves higher airway concentrations than multiple daily dosing [68]. The general applicability of once daily dosing is, however, pending.…”
Section: Penetration Of Antibiotics Into Respiratory Secretions and Pmentioning
confidence: 99%
“…Indeed, 12 hourly high peak aminoglycoside dosing has been shown to be less toxic and equally efficacious as 8 hourly dosing [103]. Similarly, a study comparing once daily with thrice daily intravenous tobramycin suggested that once daily tobramycin combined with three injections of ceftazidime is safe and effective in CF [68]. To fully answer the question on efficacy and toxicity in this context, a multicentre study is currently being carried out in the UK.…”
Section: Intravenous Antipseudomonal Antibiotic Therapy In Cystic Fibmentioning
confidence: 99%
“…6,11,[44][45][46][47][48][49][50][51][52][53][54][55][56] This regimen also was investigated in neonates up to 1 month of age but is not discussed here due to the decreased renal function in that patient population. Infectious processes included neutropenic fever, suspected or confirmed gramnegative infections, cystic fibrosis, and suspected or confirmed surgical infections.…”
Section: Efficacy In Childrenmentioning
confidence: 99%
“…8 In light of the emergence of safety and efficacy data in the CF population, the Cystic Fibrosis Foundation deemed once-daily aminoglycoside dosing as acceptable for Pseudomonas aeruginosa (grade C recommendation) in its September 2009 pulmonary exacerbation guidelines. [9][10][11][12][13][14][15][16][17][18] A 2009 survey of United States pediatric CF centers and affiliate programs distributed after the publication of these guidelines reported the use of EID (with once-daily or twice-daily dosing) in the pediatric CF population to be 94%, a significant increase from previous reports. 19 While empiric evidence suggests the use of EID of aminoglycosides to be increasingly common in the United States CF population, the prevalence of EID use across United States adult CF centers as well as the dosing and monitoring practices associated with this regimen following publication of the CF pulmonary exacerbation guidelines remain to be elicited.…”
Section: Introductionmentioning
confidence: 58%
“…This likely reflects the availability of well-designed safety and efficacy studies and meta-analyses evaluating tobramycin EID in this population, and the lack of published research studies assessing the use of gentamicin and amikacin EID in those with CF. 10,11,[13][14][15][16][17][18] As in the pediatric CF population, empiric dosing of tobramycin was most commonly prescribed at 10 mg/kg/d. 19 This practice is consistent with the dose used in a large, randomized, controlled, noninferiority study published in 2005.…”
Section: Discussionmentioning
confidence: 99%